A adolescência e a prática religiosa em grupos católicos na cidade do Recife: uma leitura psicanalítica. - Araújo, Rita de Cássia Albuquerque (2009)
The study of adolescence and appropriate ways of dealing whit this phase of life, as widely researtched is actuality, is an inexhaustible subject and has attracted huge interest from scholars of the humanities and social sciences. The religion that follows the life of the man since the beginning of its history on earth is the object of study of many sciences and has, for several centuries, a crucial role as model of life and social coexistence. Today, however, clearly feels the need to seek new forms os religious practices, which provide a contemporary approach to the man with the sacred and religious experiences. The aim of this study was to understand the religious practice offers young people that contact whit the Transcendent and the other, giving them a sense of belonging and serving as a web of support and protection against the excesses cammon to adolescence. Participants were adolescents participating in youth groups linked to the Catholic Church, and one class of peoples and other middle-class in the city of Recife. We use it to the semi-structured reviewed in the light of psychoanalytic theory. We hope that the results presented extend the the discussion and knowledge on the subject, offering subsidies to those dealing directly on indirectly with what regard to their religiosity.